(untitled) (Journal of Bio-Science, 2023)
Prostate-Specific Antigen (PSA) is a prostate cancer tumor marker, but furthermore, studies have revealed that many people with benign prostatic issues or other conditions have high PSA levels in their blood. As a result, various approaches have been suggested to boost prostate-specific antigen specificity. The aim of the study to determine whether the free-to-total PSA ratio (percent fPSA) is able to be utilized to discriminate between prostate cancer and benign prostatic hyperplasia. From December 2018 to November 2022, 260 males with Lower Urinary Tract Symptoms (LUTS) symptoms attended Rajshahi Medical College Hospital in Bangladesh were recruited purposively for a cross sectional study as per inclusion criteria. Digital Rectal Examination (DRE) and transrectal ultrasonography were performed along with age analysis. Before any manipulation, total PSA, free PSA, and percent free PSA were assessed. Transrectal ultrasound-guided biopsy or digitally guided biopsy was used to confirm the diagnosis. SPSS 26 was used to analyze the data. Among the 260 individuals, 105 were diagnosed with prostate cancer and the remaining 155 were diagnosed with benign prostatic hyperplasia. Patients with CaP were much older than those with Benign Prostatic Hyperplasia (BPH) (Mean±SD was 72±4.4 vs. 64±6.6 years, respectively) (p = 0.00001). The sensitivity, specificity, and positive predictive value of % free PSA (at cut off point 0.16) were greater (94%, 93%, 90% respectively) than those of total PSA (84%, 48%, 52% respectively). The proportion of false positives was lower in percent free PSA (10%) than in tPSA (19%). All of these considerations are critical in establishing the appropriateness of a screening test. In case of percent free PSA, the overall accuracy was 93%, significantly higher than tPSA (62%) (p<0.005). Thus, the free/total/ serum PSA ratio assists more accurately in differentiating BPH from prostate cancer. When compared to tPSA, the fPSA/tPSA and ratio enhance the discrimination between BPH and CaP comparable and are equally beneficial in lowering the incidence of unnecessary biopsies, but tPSA alone has less impact. J. Bio-Sci. 30(2): 67-77, 2022